Intercontinental study on pre-engraftment and post-engraftment Gram-negative rods bacteremia in hematopoietic stem cell transplantation patients: Risk factors and association with mortality. Issue 6 (December 2020) - Averbuch, Diana; Tridello, Gloria; Hoek, Jennifer; Mikulska, Malgorzata; Pabst, Thomas; Yaňez San Segundo, Lucrecia; Akan, Hamdi; Özçelik, Tülay; Donnini, Irene; Klyasova, Galina; Botelho de Sousa, Aida; Zuckerman, Tsila; et al.
Highlights: Center` fluoroquinolone prophylaxis allo-HSCT policy does not influence pre-engraftment Gram-negative rods bacteremia (GNRB) rate. Low post-engraftment GNRB rate in allo-HSCT patients in JACIE/FACT-accredited centers. High pre-engraftment GNRB rate in auto-HSCT patients with autoimmune diseases. Low pre-engraftment GNRB rate in auto-HSCT centers with active infection control team. MDR GNRB associated with increased post-HSCT mortality. Summary: Objectives: We present here data on Gram-negative rods bacteremia (GNRB) rates, risk factors and associated mortality. Methods: Data on GNRB episodes were prospectively collected in 65 allo-/67 auto-HSCT centers in 24 countries (Europe, Asia, Australia). In patients with and without GNRB, we compared: demography, underlying disease, HSCT-related data, center` fluoroquinolone prophylaxis (FQP) policy and accreditation status, and involvement of infection control team (ICT). Results: The GNRB cumulative incidence among 2818 allo-HSCT was: pre-engraftment (pre-eng-allo-HSCT), 8.4 (95% CI 7–9%), post-engraftment (post-eng-allo-HSCT), 5.8% (95%CI: 5–7%); among 3152 auto-HSCT, pre-eng-auto-HSCT, 6.6% (95%CI: 6–7%), post-eng-auto-HSCT, 0.7% (95%CI: 0.4–1.1%). GNRB, especially MDR, was associated with increased mortality. Multivariate analysis revealed the following GNRB risk factors: (a) pre-eng-allo-HSCT: south-eastern Europe center location, underlying diseases not at complete remission, and cord blood source; (b) post-eng-allo-HSCT: center location not in northwestern Europe; underlying non-malignant disease, not providing FQP and never accredited. (c) pre-eng-auto-HSCT: older age, autoimmune and malignant (vs. plasma cell) disease, and ICT absence. Conclusions: Benefit of FQP should be explored in prospective studies. Increased GNRB risk in auto-HSCT patients transplanted for autoimmune diseases is worrying. Infection control and being accredited are possibly protective against bacteremia. GNRB are associated with increased mortality.